Pediatric Toxidrome Simulation Curriculum: Lidocaine-Induced Methemoglobinemia - Chelsea Del Rosso; Anita Thomas; Nicole Hardy; Scott Connelly; Ulysses Davila; Jean Pearce; Suzan Mazor; Rebekah Burns (Association of American Medical Colleges, 2021)
Introduction Lidocaine is a common local anesthetic used during minor procedures performed on pediatric patients. A rare but toxic and life-threatening side effect of lidocaine is methemoglobinemia. It should be considered in children who are hypoxic after exposure to an oxidizing agent. Methods We developed this simulation case for pediatric emergency medicine (PEM) fellows, but it can be adapted for interprofessional simulation. The case involved a 1-month-old male with hypoxia and resulting central cyanosis after exposure to lidocaine. The team performed an initial evaluation and intervention, collected a history, and developed a differential diagnosis for hypoxia and central cyanosis in an infant. Methemoglobinemia was confirmed by CO-oximetry. Preparatory materials, a debriefing guide, and scenario evaluation forms assisted with facilitation. Results Fifty-six participants (including 18 PEM fellows) completed this simulation across four institutions. Participants rated the scenario on a 5-point Likert scale (1 = strongly disagree, 5 = strongly agree), finding it to be relevant to their work (median = 5) and realistic (median = 5). After participation in the simulation, learners felt confident in their ability to recognize methemoglobinemia (median = 4) and implement a plan to stabilize an infant with hypoxia (median = 4). Discussion This simulation represents a resource for learners in the pediatric emergency department. It teaches the recognition and management of an infant with lidocaine toxicity and resultant methemoglobinemia. It uses experiential learning to teach and reinforce a systematic approach to the evaluation and management of a critically ill infant with acquired methemoglobinemia.